COVID-19: A Novel Framework to Globally Track Coronavirus Infected Patients using Blockchain - Rimsan, M. (Institute of Electrical and Electronics Engineers Inc., 2020)
An outbreak of coronavirus caused by a novel virus called SARS-CoV-2 occurred at the end of 2019. The unexpected outbreak and unchecked global spread of COVID19 indicate that the current global healthcare networks have limitations in addressing the crises for public safety. The detection of infected or tested patients globally is challenging when patients travel abroad. As such, innovative technology such as blockchain has emerged as a potential approach for addressing coronavirus patient tracking. Blockchain technology can tackle pandemics by allowing early detection of outbreaks, protecting individual privacy while maintaining data security by using smart contracts. Motivated by these facts, we propose a novel blockchain-based framework that integrates intercountry for COVID-19 to track infected or tested patients globally using the methodology of design science research. The proposed framework could help governments, aviation industries, health authorities, and residents make essential decisions on infection identification, infection prediction, and infection prevention. Â© 2020 IEEE.